Ideology in the Korean War - Elias Daton Kopong; Pujo Widodo; Ikhwan Syahtaria; Achmed Sukendro (Formosa Journal of Social Sciences (FJSS), 2024)
This study examines the persistent tensions between North and South Korea, two nations that share historical and cultural ties prior to their division following World War II. After Japan’s surrender on August 15, 1945, Korea was split into two spheres of influence: the Soviet Union took control of the North, while the United States oversaw the South, with the 38th parallel serving as the dividing line. This division led to stark ideological, social, and economic differences between the two countries, exacerbated by the Cold War rivalry. The Korean War became a larger proxy conflict, with North Korea receiving support from the Soviet Union and China, while South Korea was backed by the United States and its UN allies. The war involved various military strategies across land, sea, and air, adapting to the evolving battlefield conditions. This research uses a descriptive analysis and documentary method, relying on books, articles, and other sources to explore the ongoing conflict and the challenges of the peace process between the two Koreas. The study aims to illuminate the root causes of the conflict and the barriers to lasting peace, while emphasizing the substantial role of global powers like the United States and the Soviet Union in shaping the ideological and social dynamics of the Korean Peninsula